Epistulae ex Ponto. Book I - Ovidius Naso, Publius; Tissol, Garth, 1953- (Cambridge : Cambridge university press, 2014)
"When Ovid, already renowned for his love poetry, the Metamorphoses and other works, was exiled by Augustus to Tomis on the Black Sea in AD 8, he continued to write. After five books of Tristia, he composed a collection of verse letters, the Epistulae ex Ponto, in which he appeals to his friends and supporters in Rome, lamenting his lot and begging for their help in mitigating it. In these epistolary elegies his inventiveness flourishes no less than before and his imaginative self-fashioning is as ingenious and engaging as ever, although in a minor key. This commentary on Book I assists intermediate and advanced students in understanding Ovid's language and style, while guiding them in the appreciation of his poetic art. The introduction examines the literary background of the Epistulae ex Ponto, their relation to Ovid's earlier works, and their special interest and appeal to readers of Augustan poetry"--
"In the modern revival of interest in Ovid's exilic poetry, the Tristia have long received the most attention, although his last elegies, the Epistulae ex Ponto, reward the reader no less and are arguably more appealing - works in which his inventiveness flourishes no less than before, and in which his imaginative self-fashioning is as ingenious and engaging, though now in a minor key, as it was always was from the time of his Amores. Their comparative neglect resulted partly from a dearth of commentaries. Whereas Luck's commentary on the Tristia (1967, 1977) long made that collection more accessible, the reader of the Epistulae ex Ponto had until recently little beyond Keene (1887) in English and Scholte (1933) in Latin on book 1, both difficult to obtain. Now, however, Ovid's readers can look forward to the completion of M. Helzle's German commentary on all four books, of which the first volume, on books 1-2, appeared in 2003; his commentary on selected elegies of book 4 (1989) is in English. On book 2 we have Pérez Vega (1985) in Spanish and Galasso (1995) in Italian. In 2005 appeared J. F. Gaertner's commentary in English on book 1, a valuable work, whose vast scale perhaps diminishes its accessibility to some readers.
Sadrži tekst na lat. i komentar na eng.
Bibliografija: str. 181-186
Kazala
Text in Latin, commentary in English.
Keywords: Ovidije - komentar